Legal Certainty Regarding The Cancellation Of Arbitration Awards In District Courts - Juniarty, Santy; Setiawan, Puguh Aji Hari; Iryani, Dewi (jurnal.unprimdn.ac.id, 2025)
Arbitration in Indonesia, based on Law Number 30 of 1999, is designed as a dispute resolution mechanism that provides legal certainty through its final and binding decisions. This principle, known as das sollen, is expected to support a conducive investment climate. However, in practice (das sein), Article 70 of the same law authorizes the District Court to annul arbitration awards. The implementation of this authority, particularly on grounds of